2018
DOI: 10.7324/japs.2018.81007
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of resveratrol ameliorates epidermal hyperplasia in ultraviolet B irradiated BALB/c mice

Abstract: Commercial sunscreens contain cosmetic preservatives which could exert phototoxic effect when exposed to sunlight. Natural sources, such as resveratrol, have gain attention in the cosmetic world as it has higher antioxidant capacity than vitamins C and E. Resveratrol also possesses strong anti-inflammatory, anti-cancer, and anti-aging properties. It also has proven to reduce epidermal hyperplasia and skin thickness. The aim of the study was to evaluate the ameliorative effect of resveratrol in reducing epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The dose was freshly prepared daily by dissolving L-glutathione in corn oil and then vortexing it until the powder dissolved completely. All mice were fasted for 4 h before being treated with 0.2 ml of dissolved glutathione by oral gavage [19].…”
Section: Methodsmentioning
confidence: 99%
“…The dose was freshly prepared daily by dissolving L-glutathione in corn oil and then vortexing it until the powder dissolved completely. All mice were fasted for 4 h before being treated with 0.2 ml of dissolved glutathione by oral gavage [19].…”
Section: Methodsmentioning
confidence: 99%
“…Resveratrol is a polyphenol present in red wine, grapes, berries, pomegranates and peanuts, that has been reported to possess pharmacological activities such as antioxidant, anti-inflammatory, anti-aging and anti-cancer effects [ 101 , 102 ]. Numerous studies have demonstrated consistent neuroprotective effects of resveratrol in AD models due to mechanisms such as inhibition of Aβ plaque accumulation and hyperphosphorylation of tau protein [ 103 ].…”
Section: Natural Product-derived Nanoparticles and Their Therapeutic ...mentioning
confidence: 99%